If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19b + -17b = 12 Combine like terms: 19b + -17b = 2b 2b = 12 Solving 2b = 12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '2'. b = 6 Simplifying b = 6
| 5x+24=3x+8 | | 16,5+x/2=20 | | 2a/3=6 | | 2x*-4=-1/2*x+6 | | 8[50s]= | | 18u+-10u+-2y=18 | | 3c^2+3=-10c | | -3500+60x=0-90x | | 0-90x=-3500 | | 2g+4g-2g-g=18 | | 9[70s]= | | 2X-4=-0.5X+6 | | 16+17*3+x=20 | | 13h-12h+4h+2h+3h=10 | | 9[7s]= | | 1/3a=6 | | 16+17+x*3=20 | | 7(x-19)=7*3 | | 16+17/2+x=20 | | (1/2)*y+3=9 | | 1/2y+3+9 | | 7x^2-8y=84x-2y^2-176 | | 3-ln(x+5)=ln(x-6) | | 4a-b=14 | | 11+10+x=20 | | n+7n=56 | | 11+10+x/3=20 | | 15=-d+11 | | 9(x-2)=54.9 | | 8(x-3)=8 | | 11+8+x/3=20 | | 40.6=6c-5 |